Decellularized bone extracellular matrix and human dental pulp stem cells as a construct for bone regeneration. Issue 8 (24th May 2017) - Paduano, Francesco; Marrelli, Massimo; Alom, Noura; Amer, Mahetab; White, Lisa J.; Shakesheff, Kevin M.; Tatullo, Marco
Abstract: Dental pulp tissue represents a source of mesenchymal stem cells that have a strong differentiation potential towards the osteogenic lineage. The objective of the current study was to examine in vitro osteogenic induction of dental pulp stem cells (DPSCs) cultured on hydrogel scaffolds derived from decellularized bone extracellular matrix (bECM) compared to collagen type I (Col-I), the major component of bone matrix. DPSCs in combination with bECM hydrogels were cultured under three different conditions: basal medium, osteogenic medium and medium supplemented with growth factors (GFs) and cell growth, mineral deposition, gene and protein expression were investigated. The DPSCs/bECM hydrogel constructs cultured in basal medium showed that cells were viable after three weeks and that the expression of runt-related transcription factor 2 ( RUNX - 2 ) and bone sialoprotein ( BSP ) were significantly upregulated in the absence of extra osteogenic inducers compared to Col-I hydrogel scaffolds. In addition, the protein expression levels of BSP and osteocalcin were higher on bECM with respect to Col-I hydrogel scaffolds. Furthermore, DPSCs/bECM hydrogels cultured with osteogenic or GFs supplemented medium displayed a higher upregulation of the osteo-specific markers compared to Col-I hydrogels in identical media. Collectively, our results demonstrate that bECM hydrogels might be considered as suitable scaffolds to support osteogenic differentiation of DPSCs.